The Ethanolic Extract of Annonaceous sp. to Inhibit Vascular Endothelial Growth Factor (VEGF) as Anticancer Modalities - Muhartono Muhartono; Asep Sukohar; Khairun Nisa; Ratna Dewi Puspita Sari; Suharyani; Arli Suryawinata (HM Publisher, 2021)
Introduction: Cancer has become a major public health problem worldwide, with breast cancer is the most common cancer among women and one of the most important causes of death among them. Management of breast cancer have some adverse effects, with many factorx=s shiouln be considered to ordered the therapy. Use of chemotherapy will suppress cell proliferation and trigger apoptosis, but it cannot just focus on cancer cells only, but also would affected on other cells and cause. Objective: This study aim to analyze the inhibition effect of the Annonanceous sp. ethanolic extract to Vascular Endothelial Growth Factor (VEGF) on MCF-7 cells line Material and Methods: This study is an analytic experimental study used Randomized Complete Block Design (RCBD) with three repetitions. The extract was dissolved in 1 ml of DMSO with a concentration of 0.1%. Furthermore, dilution was made with a dose of 0 µg / ml (K); 25 µg / ml (P1); 50 µg / ml (P2); 100 µg / ml (P3); 200 µg / ml (P4). MCF-7 cells line were cultured used RPMI 1640 Medium with 80 – 90% confluent. The ethanolic extract of Annonaceous sp. were exposed to MCF-7 cells for 48 hours. Analyze of VEGF level use ELISA Methods with λ=405 nm. Results: The results of ELISA analyze shows that the ethanolic extract of Annonaceous sp. have potential effect to decreased of VEGF expression on sample with treatment on some concentration (p< 0,05). Conclusion: The ethanolic extract of Annonaceous sp. has shows the potential effect to decreased of VEGF level on MCF-7 cells line